Alpha-lipoic acid reduces body weight and regulates triglycerides in obese patients with diabetes mellitus - Azra Okanović; Besim Prnjavorac; Edin Jusufović; Rifat Sejdinović (Medicinski glasnik, 2015)
Aim: To determine an influence of alpha-lipoic acid to reduction of body weight and regulation of total cholesterol concentration, triglycerides and glucose serum levels in obese patients with diabetes mellitus type 2. Methods: A prospective study includes two groups of obese patients with diabetes mellitus and signs of peripheral polyneuropathia: examined group (30 patients; 15 females and 15 males), and control group (30 patients; 12 females and 18 males). All were treated with metformin (850-1700 mg/day). Examined patients were additionally treated with alpha-lipoic acid 600 mg/day during 20 weeks. Body mass index and concentrations of total cholesterol, triglycerides and glucose in serum were compared before and after the treatment. Results: The group treated with 600 mg alpha-lipoic acid lost significantly more weight, and had lower triglyceride level than the control group. There were no significant differences in total cholesterol and glucose serum levels between the groups. Conclusion: Alpha-lipoic acid of 600 mg/day treatment have influenced weight and triglycerides loss in obese patients with diabetes mellitus type 2. It should be considered as an important additive therapy in obese patients with diabetes mellitus type 2.
Keywords: body mass index; serum glucose; lipid status.